Acceptance of mobile health in medical sciences students: Applying technology acceptance model - Mahnaz Samadbeik; Nasim Aslani; Masoumeh Maleki; Ali Garavand (Informatics in Medicine Unlocked, 2023)
Introduction: Mobile health (mHealth) is a crucial technology that plays a pivotal role in improving the quality of healthcare services. This study aimed to identify the effective factors in the acceptance of mHealth among medical sciences students in Iran, according to Technology Acceptance Model (TAM). Methods: A cross-sectional study was conducted in 2019, involving students from a medical sciences university in Iran. Participants were selected through simple random sampling, and a total of 300 completed questionnaires were collected. The data were gathered using the standard questionnaire of the TAM. Data analysis was performed using statistical tests such as independent sample t-test, ANOVA analytical tests, correlation, and regression in SPSSv26 software. Results: The results show that there was no significant relationship between sex and latent variables (p > 0.05). However, a significant relationship was observed between perceived ease of use (PEU) (p = 0.001) and perceived usefulness (PU) (p < 0.001) with attitude to use (AU), as well as between AU and behavioral intention (BI) (p < 0.001). Conclusion: It is suggested that policymakers consider the PEU and PU of mHealth when designing and implementing it formally for students and healthcare providers as the main mHealth stakeholders.